The Prevalence of Sexual and Gender Minority Youth in the Justice System: A Systematic Review and Meta-Analysis. (July 2019) - Jonnson, Melissa R.; Bird, Brian M.; Li, Shanna M. Y.; Viljoen, Jodi L.
Theoretical models, such as the minority stress model, suggest that sexual and gender minority (SGM) youth may be overrepresented in the justice system. However, few studies have examined rates of SGM youth in the system, and even fewer have compared them with rates of these youth in the broader community. To obtain a more accurate estimate, we conducted a systematic review and meta-analysis of 31, 258 youths and compared rates of SGM youth in the justice system with those in the community. Contrary to claims that SGM youth are overrepresented generally, this review suggests that sexual minority girls, specifically, are disproportionally involved in the justice system. Rates of involvement appeared to differ across ethnic subgroups of sexual minority youth, and evidence is inconclusive regarding the prevalence of gender minority youth in the system. Implications of these findings for researchers and justice system professionals are discussed.